Feed Insects as a Reservoir of Granadaene-Producing Lactococci - Neuzil-Bunesova, Vera; Ramirez Garcia, Alejandro; Modrackova, Nikol; Makovska, Marie; Sabolova, Monika; Spröer, Cathrin; Bunk, Boyke; Blom, Jochen; Schwab, Clarissa (Frontiers in Microbiology, 2022)
Insects are a component of the diet of different animal species and have been suggested as the major source of human dietary protein for the future. However, insects are also carriers of potentially pathogenic microbes that constitute a risk to food and feed safety. In this study, we reported the occurrence of a hemolytic orange pigmented producing phenotype of Lactococcus garvieae/petauri/formosensis in the fecal microbiota of golden lion tamarins (Leontopithecus rosalia) and feed larvae (Zophobas atratus). Feed insects were identified as a regular source of L. garvieae/petauri/formosensis based on a reanalysis of available 16S rRNA gene libraries. Pan-genome analysis suggested the existence of four clusters within the L. garvieae/petauri/formosensis group. The presence of cyl cluster indicated that some strains of the L. garvieae/petauri/formosensis group produced a pigment similar to granadaene, an orange cytotoxic lipid produced by group B streptococci, including Streptococcus agalactiae. Pigment production by L. garvieae/petauri/formosensis strains was dependent on the presence of the fermentable sugars, with no pigment being observed at pH <4.7. The addition of buffering compounds or arginine, which can be metabolized to ammonium, restored pigment formation. In addition, pigment formation might be related to the source of peptone. These data suggest that edible insects are a possible source of granadaene-producing lactococci, which can be considered a pathogenic risk with zoonotic potential.